The Effect of Convenience, Benefits, and Risks on Interest in Using Brimo Mobile Banking Services in Mantup District - Riski Hadian; Evi Fitrotun Najiah; Mohammad Yaskun (Sean Institute, 2024)
This study aims to determine the influence of convenience, benefits and risks on interest in using mobile banking services in a case study in Mantup District. This type of research is quantitative research. The population in this study is BRImo application users in Mantup District. Sampling in this study is based on Lemeshow's research formula obtained from 96 samples. The tests in this study used validity test analysis tools, reliability test, multiple linear regression test, multiple correlation test, determination coefficient test, partial test (t test), and simultaneous test (F test). The results of the study showed that the variables of convenience, benefit, and risk had a partial or simultaneous and significant effect on the variables of interest in using the BRImo service. Benefits were the most dominant variable in this study.